Family Support for Healing Mental Disorder Patients with Social Isolation in the Work Area of Pasirkaliki Public Health Center, Bandung City - Zaenal Muttaqin; Muryati Muryati; Dadang Purnama; Rukman Rukman (Utan Kayu Publishing, 2022)
The research with the title: Family Support for the Recovery of Mental Patients with Social Isolation in the Pasirkaliki Bandung Health Center Work Area in 2021, aims to identify differences in family support for the recovery of mental patients with social isolation before and after being given training and assistance. The research method used is quasi-experimental with one group pretest and posttest design with bivariate test using T-test. The population in this study was all families who had family members with mental disorders (social isolation) recorded at the Pasirkaliki Health Center in Bandung from January-June 2021 with a sample of 35 people. The results of the study after the provision of material and assistance by researchers are that there are significant differences in the level of physiological adaptation before and after health education is carried out where p-v = 0.001, there were significant differences in the level of adaptation of self-concept before and after the implementation of health education where the value of p-v = 0.045, there was no significant difference in the level of interdependence adaptation before and after the implementation of health education where the value of p-v = 0.068. The conclusion of this study is that there is an increase in family support for the recovery of mentally disturbing patients with social isolation after providing material and assistance to families in the care of social isolation patients, both physiological support, self-concept support and interdependence support. Likewise, the total adaptation support provided by families to mental patients with social isolation. The suggestion in this study is for the Puskesmas to hold trainings to improve the performance of its employees in the mental nursing service unit to further increase knowledge and understanding so that it can be applied to the community in developing.